Justice League starcrossed - Lukic, Butch; Riba, Dan; Fogel, Rich; Ridely, John; McDuffie, Dwayne; Timm, Bruce; Tucker, James (DC kids collection., 2004)
When a Thanagarian spaceship descends upon Earth, the Justice League turns to Hawkgirl for some answers. And their questions multiply when they discover she has been living amongst them as a spy! As the Thanagarian visitors reveal their dark intentions, Hawkgirl must choose between loyalty to her people and love for her friends on her adopted planet Earth.